RISK MANAGEMENT OF WAKAF MANAGEMENT INSTITUTIONS - Siagian, Salsabilla; Nasution, Inayatul Widad; Sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2024)
Waqf has great potential in the sharia financial sector, it can accelerate the development of infrastructure, social facilities and religious facilities. Risk management is crucial in waqf management. Reputational, operational, distribution and transfer risks between countries need to be identified and addressed. Risk management can increase public trust, minimize losses, and ensure sharia compliance. The urgency of risk management lies in providing risk information to regulators, ensuring operational continuity, and measuring risk exposure. It requires strengthening human resources, increasing transparency, applying information technology, cross-border collaboration, and regular audits to ensure compliance and effectiveness of risk management. The development of productive waqf products is expected to increase the income potential and long-term benefits of waqf assets.